Assessment competency among primary English language teachers in Malaysia - Wan Mohd Mahfodz bin Wan Hasan (Kulliyyah of Education, International Islamic University Malaysia, 2016)
Assessment for Learning (AfL) has been implemented in Malaysian Schools in 2011 with attempts to (i) achieve the aspiration of national Philosophy of Education towards developing learners' physical, emotional, spiritual and intellectual abilities, (ii) reduce exam oriented learning, (iii) evaluate learners' learning progress and (iv) enhance teachers' integrity in assessing, recording, and reporting learners' learning. The purpose of this study is (i) to establish whether primary educators' self-reported assessment practices constituted meaningful and interpretable dimensions of AfL (ii) to determine the relative frequency of AfL practices among the primary educators and (iii) to determine their perceived competencies in relevant aspects of AfL namely perceived monitoring and perceived scaffolding practices. A set of questionnaires consisted of 28 items on 5 point scale of frequency was used to collect data from 120 respondents which have been selected conveniently from Wilayah Persekutuan Kuala Lumpur. Data were analysed using descriptive and inferential statistics. Overall result showed encouraging results where most practices of AfL were frequently practiced. However, there are some concerns in practices involving scaffolding. English teachers seem to practice significantly more scaffolding than monitoring. Additionally, the effect of the gender was found to be statistically significant on the level of practices, that is female English teachers tend to monitor students' progress more than male teachers. The implications of the results that underpin AfL are discussed in relation to teachers' competency and training needs. Keyword: Classroom Assessment, Assessment for Learning, Scaffolding Practices, Monitoring Practices, Assessment Feedback.